Implementation of Hadrah Extracurricular Arts in Increasing the Spirit of Reciting Santri and Santriwati TPA Raudlatul 'Ulum Timbul Rejo Bangunrejo Subdistrict - Wibowo, Wahyu Hadi; Damilu, Silfana (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2025)
Low interest in learning the Qur'an among children is a recurring challenge in many Islamic education institutions, often resulting in reduced motivation and weak learning outcomes. This study aims to examine the implementation of hadrah-based extracurricular activities as a strategy to improve students' enthusiasm and engagement in learning the Qur'an at Raudlatul 'Ulum Qur'anic Education Park, Timbul Rejo, Bangunrejo District. Employing a qualitative case study approach, data were collected through observation, interviews, and documentation. The findings indicate that the integration of hadrah, a traditional Islamic musical art form, into extracurricular programs successfully increased students’ learning interest and attendance. The activities, scheduled on weekends, contributed to developing students’ motivation, discipline, and appreciation of Islamic values through creative expression. This study implies that culturally relevant extracurricular activities can serve as effective tools in strengthening religious education and character building among students in non-formal Islamic education settings.